2021
DOI: 10.1038/s41467-021-24329-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and selective oxygen reduction to H2O2 on boron-doped carbon for high production rates

Abstract: Oxygen reduction reaction towards hydrogen peroxide (H2O2) provides a green alternative route for H2O2 production, but it lacks efficient catalysts to achieve high selectivity and activity simultaneously under industrial-relevant production rates. Here we report a boron-doped carbon (B-C) catalyst which can overcome this activity-selectivity dilemma. Compared to the state-of-the-art oxidized carbon catalyst, B-C catalyst presents enhanced activity (saving more than 210 mV overpotential) under industrial-releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(187 citation statements)
references
References 53 publications
(78 reference statements)
4
157
0
Order By: Relevance
“…and 138 mV dec -1 , respectively. The higher the Tafel slope, the faster the overpotential increases with current density [23]. Tafel slopes that significantly exceed 120 mV dec -1 are generally an indication that there are mass transfer problems that confound the kinetics mV dec -1 and 100 mV dec -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and 138 mV dec -1 , respectively. The higher the Tafel slope, the faster the overpotential increases with current density [23]. Tafel slopes that significantly exceed 120 mV dec -1 are generally an indication that there are mass transfer problems that confound the kinetics mV dec -1 and 100 mV dec -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tafel slopes that significantly exceed 120 mV dec -1 are generally an indication that there are mass transfer problems that confound the kinetics mV dec -1 and 100 mV dec -1 , respectively. For these materials, a slope below 120 mV dec -1 indicates that the electrochemical reaction is capable of obtaining a high current density with low potential [23].…”
Section: Resultsmentioning
confidence: 99%
“…S12, the 2e − ORR catalytic activity of the O-BC materials increases with annealing temperature from 550 to 650°C, with O-BC-2-650 exhibiting the highest H 2 O 2 selectivity; when the temperature exceeds 650°C (i.e., O-BC-2-700), the 4e − ORR pathway is promoted. The excellent H 2 O 2 selectivity of O-BC-2-650 can be attributed to its abundance of doped boron sites and porous structure [19,31]. The electrochemical stability of O-BC-2-650 was investigated by the steady-state polarization method.…”
Section: H 2 O 2 Selectivity Of O-bcmentioning
confidence: 99%
“…In addition to the above-mentioned heteroatom dopants, boron has a lower electronegativity (2.04) than that of carbon (2.55). Thus, a B site is positively charged when situated adjacently to a C site, facilitating the chemisorption of O 2 molecules and promoting the ORR at B instead of nearby C sites [29][30][31]. Nevertheless, the use of self-initiative heteroatom dopants like B to promote the 2e − ORR remains relatively under researched.…”
Section: Introductionmentioning
confidence: 99%
“…Although plenty of pioneering studies investigating H2O2 production in several particulate systems have been reported, such as foreign chemical doping, surface defects controlling, various heterogenization and molecular architecture modulation, most of them still exhibited general, relatively poor efficiencies of H2O2 production [6][7][8][18][19][20][21] . The ineffective hole scavenging via water oxidation and the resulting charge recombination often necessitates the addition of organic electron donors [22,23] . Besides, low selectivity toward H2O2 synthesis via twoelectron O2 reduction compared to the four-electron reduction of O2 or two-electron H2 evolution required manipulating noble metallic sites as cocatalysts to improve both the activity and selectivity of H2O2 production [19,[24][25][26] .…”
Section: Introductionmentioning
confidence: 99%